The Role of Islamic Banking, Macroeconomics Factor, and Regulation in Islamic Moral Economy: Evidence from OIC Countries Using Panel GMM - Titis Miranti; Zulfa Muasaroh Binti Rahmawati; Kurniawati Meylianingrum; Tiara Juliana Jaya; Ahmad Tibrizi Soni Wicaksono (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025